Web GIS and Mapping - Veenendaal, Bert (Springer, 2013)
The Internet and web-based technology has dramatically influenced the access to and dissemination of information among communities, locally and globally. This is no less true in the domain of geographic information systems (GIS) which have traditionally been constrained in terms of information access and the communities that use them. Geospatial data has traditionally been captured and managed within individual and separate organizational databases with access by a limited number of expert users. Now, with the integrated use of the web, not just geospatial data, but also the functionality of GIS can be accessed globally by citizens and non-experts.